PERLINDUNGAN HAK MASYARAKAT ADAT TERHADAP PEMANFAATAN HUTAN DAN IMPLIKASI HUKUMNYA - Sulbadana, Sulbadana (AKTUALITA, 2011)
International law insists that the sovereignty of indigenous peoples innatural resources management is a right that must be protected where thestate or the government is obliged to make it happen. The consideration oflaw and philosophy in giving the indigenous peoplesprotection in exploiting the natural resources because the indigenouspeoples have cultural values and local wisdom based on SustainableDevelopment Principle. It means that the establihment of a certain forestas a conservation area like the Lore Lindu National Park should not becontrary and detrimental to the welfare of the people around that area asthe indigenous peoples were still exist from generation to generation andhave a close relationship in emotion with the forest.Keywords: Sustainable Development Principle, Indigenous Peoples,international environment law.